Structural variation of dinuclear transition metal compounds with a common type of ligand: solid state and solution structures and model studies - Comba, Peter (Inorganic chemistry, 1999)
The structural properties of the four-coordinate dinickel(II) and the (4 + 1)-coordinate dicopper(II) compounds of two bis(diamine-diamide) ligands, based on the condensation of 1,8-diamino-3,6-diazaoctane or ethane-1,2-diamine with bismalonic esters (that is the complexes of the bis-13-membered macrocyclic ligand L1 and of the corresponding open-chained ligand L2) are studied by X-ray crystallography, EPR spectroscopy, and molecular modeling. X-ray crystallography indicates that Cu2L1(OH2)2 and Cu2L2(OH2)2 have a stretched conformation (torsion angle φ(M−Cbridgehead−C‘bridgehead−M‘) = 180°); Ni2L2 has the same stretched conformation, but Ni2L1 is folded (φ(M−Cbridgehead−C‘bridgehead−M‘) = 55°). The dicopper(II) compounds have the same stretched structure in solution (MM-EPR), and molecular mechanics studies (strain energy as a function of the torsion angle φ) indicate that the most stable conformations are those observed in the solid state and in solution, i.e., stretched for Cu2L1(OH2)2, Cu2L2(OH2)2, and Ni2L2 and folded for Ni2L1. Reasons for the stabilization of the observed structures are discussed in detail.